Adsorbed natural gas storage by experimental and simulation approaches - Al-Khatib, Ma'an Fahmi Rashid (IIUM Press, International Islamic University Malaysia, 2017)
Adsorbed natural gas (ANG) technique was used in this study to test the adsorption capacity of carbon materials fro methane gas storage. An adsorption system based on volumetric method was designed and fabricated for this purpose. The carbon materials used were Malaysian industrial activated carbon produced from palm kernel shell and coconut shells. These materials have not been thoroughly investigated for ANG applications. Also a new material which is a composite of CNTs and activated carbon (ACNT) produced in this work along with commercial CNTs were investigated as ANG storage media. ACNT was produced using chemical vapour deposition (CVD) method using activated carbon as catalyst substrate. The presence of activated carbon, besides being substrate, served as auxiliary storage media. This method successfully produced CNTs with diameters ranged form 25 to 70 nm and lengths, mostly, of more than 10 μm. These long tubes could be a result of the long reaction time (3 hours), thus if shorter CNTs are required, shorter reaction times should be applied. The adsorption storage experiments were run at pressures up to 50 bar and temperatures of 30, 40 and 50 °C. The adsorption capacity on mass basis (at 35 bar and 30 °C) ranged from as low as 1.48 mmol/g for com-CNT to 6.20 mmol/g for CSAC3. ACNT showed a relatively high adsorption capacity of 4.51 mmol/g. The results indicate that there is a general trend of increasing in adsorption capacity with increasing micropore volume. However, micropore size distribution (MPSD) must be taken into account in evaluating the adsorbents.